Association between circulating leptin levels and multiple sclerosis: a systematic review and meta-analysis. Issue 1111 (26th March 2018) - Xie, Xue-Feng; Huang, Xiao-Hui; Shen, Ai-Zong; Li, Jun; Sun, Ye-Huan
Abstract: Aim: Leptin, synthesised by adipocytes, has been identified as a hormone that can influence inflammatory activity. Several studies have investigated leptin levels in patients with multiple sclerosis (MS), but the results are not consistent. This study aims to derive a more precise evaluation on the relationship between circulating leptin levels and MS. Design: A comprehensive literature searched up to July 2017 was conducted to evaluate the association of circulating leptin levels and MS. The random-effect model was applied to calculate pooled standardised mean difference (SMD) and its 95% CI. Main outcome measures: Circulating leptin levels of patients with MS and healthy controls. Results: Of 2155 studies identified, 33 met eligibility criteria and 9 studies with 645 patients with MS and 586 controls were finally included in the meta-analysis. Meta-analysis revealed that, compared with the healthy control group, the MS group had significantly higher plasma/serum leptin levels, with the SMD of 0.70% and 95% CI (0.24 to 1.15). Subgroup analyses suggested that the leptin levels of patients with MS were associated with region, age, study sample size, measurement type, gender and blood sample type. Conclusion: Overall, our study suggests that patients with MS have a significantly higher leptin level than in healthy controls. Further mechanism studies and longitudinal large cohort studies are still needed to further reveal the role of leptin in the pathogenesis of MS.